The use of placebo in a trial of rectal artesunate as initial treatment for severe malaria patients en route to referral clinics: ethical issues. Issue 2 (4th February 2010) - Kitua, Andrew; Folb, Peter; Warsame, Marian; Binka, Fred; Faiz, Abul; Ribeiro, Isabela; Peto, Tom; Gyapong, John; Yunus, Emran Bin; Rahman, Ridwan; Baiden, Frank; Clerk, Christine; et al.
Abstract : Placebo-controlled trials are controversial when individuals might be denied existing beneficial medical interventions. In the case of malaria, most patients die in rural villages without healthcare facilities. An artesunate suppository that can be given by minimally skilled persons might be of value when patients suddenly become too ill for oral treatment but are several hours from a facility that can give injectable treatment for severe disease. In such situations, by default, no treatment is (or can be) given until the patient reaches a facility, making the placebo control design clinically relevant; alternative bioequivalence designs at the facility would misrepresent reality and risk incorrect conclusions. We describe the ethical issues underpinning a placebo-controlled trial in severe malaria. To protect patients and minimise risk, all patients were referred immediately to hospital so that each had a higher chance of prompt treatment through participation. There was no difference between artesunate and placebo in patients who reached clinic rapidly; among those who could not, a single artesunate suppository significantly reduced death or permanent disability, a finding of direct and indirect benefit to patients in participating villages and elsewhere.